Hypovirulence caused by mycovirus in Colletotrichum fructicola - Guo, Jun; Zhou, Xinyu; Xie, Fangling; Cao, Junjie; Liu, Shuangqing; Zhong, Jie; Zhu, Hongjian (Frontiers in Plant Science, 2022)
Colletotrichum fructicola is a pathogenic fungus causing leaf black spot and fruit rot disease in a wide variety of crops. Some mycoviruses that cause detrimental effects on fungal hosts could be useful in studying the pathogenesis of fungal hosts. In this study, we reported two mycoviruses, Colletotrichum fructicola ourmia-like virus 1- Colletotrichum gloeosporioides ourmia-like virus 1 (CfOLV1-CgOLV1) and Colletotrichum fructicola ourmia-like virus 2 (CfOLV2), from a C. fructicola fungus. The complete genome sequences of CfOLV1-CgOLV1 and CfOLV2 contain 2,516 bp and 2,048 bp, respectively. Both of these viruses contain only one open reading frame (ORF), which encodes an RNA-dependent RNA polymerase (RdRp). CfOLV1-CgOLV1 was identical as the previously reported virus CgOLV1. Phylogenetic analysis showed that CfOLV2 is closely related to Scleroulivirus and Magoulivirus in the family Botourmiaviridae. Virus elimination and horizontal transmission experiments proved that the associated mycoviruses could reduce the pathogenicity of the host C. fructicola. In addition, we found that the virus-containing strains showed a much higher percentage of appressorium formation and more melanin production compared to isogenic virus-free strain, and the presence of the virus is detrimental to the growth of host fungi and regulates the integrity of the cell wall. Transcriptomic analysis showed that mycovirus infection caused various abnormal genes expression in C. fructicola. To the best of our knowledge, this is the first report of a hypovirulence-associated ourmia-like mycovirus in C. fructicola.